ROLE OF REMUNERATION AND CAREER ADVANCEMENT PRACTICES ON THE RETENTION OF EMPLOYEES IN ORGANIZATIONS: EVIDENCE FROM RESEARCH - Kinyili, Jacinta M.; Karanja, Kabare; Namusonge, G.S. (My University, 2015)
In a globalized environment, attraction and retention of high prospective employees is a huge challenge to organizations especially in times of high turnover rates. In many instances even engaged employees are sometimes dissatisfied with the human resource management practices in place which may lead them to look elsewhere. This theoretical paper investigates the role of remuneration practices and career advancement practices on the retention of employees in organization by reviewing existing theoretical and empirical evidences from textbooks and journals. Remuneration and career advancement practices that enhance employee retention have also been reviewed. The review revealed that these practices are crucial in influencing employee satisfaction hence retention. Thus organizations should formulate appropriate remuneration and career advancement practices to reduce turnover rate and increase retention rates. However these require a commitment from employers, but will be worth the investment in the long term.
Keywords: Remuneration; Career Advancement; Retention